Rancang Bangun Sistem Informasi Keuangan Sekolah di Pusdiklatkom Tanjungsari Berbasis Desktop - Agus Supriatna; Anjas Tryana (Ma'soem University, 2023)
Based on observations, that at the Tanjungsari Pusdiklatkom the process of processing financial data such as tuition payments, payment of education fees, exam payments, and recaps of money expenditures still uses a manual system. The design method used is the SDLC (System Development Life Cycle) method. Starting from the system development process to the system is applied with the Waterfall model which consists of several basic work stages, : Requirement, Analysis, Design, Coding, Testing and Maintenance. The results showed that the design of a desktop-based school financial information system at Pusdiklatkom Tanjungsari made it easier for Pusdiklatkom Tanjungsari Desktop-based makes it easier for Pusdiklatkom Tanjungsari to process its financial data.